Theoretical Foundations of Arabic Dictionary Compilation: A Systematic Sociolinguistic Literature Review - Viqri Aditya; Abdurachman Abdurachman; Syaripuddin Basyar (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2026)
This research critically examines the objectives of Arabic dictionary compilation based on theoretical approaches developed from classical to contemporary traditions, analyzing their implications for language learning and documentation. Using a qualitative literature study method, this research analyzes scientific literature published mainly within the last five years, supplemented by relevant classical lexicographical works. The literature selected as the main object of study met three inclusion criteria: (1) directly discusses Arabic dictionaries or lexicography, (2) explains the purposes, users, functions, or structure of dictionaries, and (3) is accessible via open access or verified repositories such as Google Scholar, DOAJ, and arXiv. The selected literature was analyzed using content analysis to identify the classification of dictionary objectives, their relationship with user characteristics and usage contexts, and their relevance to education and translation. Findings show that the orientation of Arabic dictionary compilation has transformed significantly, from normative documentary functions in the classical era to pedagogical instruments and linguistic technology today. A gap nonetheless remains between the theoretical approaches used and users' practical needs. This study offers a theoretical synthesis integrating classical and modern perspectives, emphasizing the need for adaptive, user-oriented dictionary objectives, contributing to more functional, contextual Arabic lexicographical models in the digital era.